Analytical strategies for chemical exposomics: exploring limits and feasibility. Issue 1 (23rd November 2021) - Vitale, Chiara Maria; Price, Elliott J; Miller, Gary W; David, Arthur; Antignac, Jean-Philippe; Barouki, Robert; Klánová, Jana
Abstract: Tackling the challenges of chemical exposomics will require the implementation of diverse analytical strategies and technological advancements. Herein, high-resolution mass spectrometry-based methods applied in current chemical exposome studies have been surveyed and are shown to be limited. Notably, liquid chromatography separations almost exclusively employ reversed-phase C18 columns using water/methanol gradients with formic acid additive, while gas chromatography is underexploited in the field at this stage. A systematic evaluation of strategies applied in related disciplines (i.e. metabolomics, proteomics, multiresidue trace analysis) was undertaken to provide practical guidance for the development of chemical exposomics. The approaches were assessed on the basis of their costs (i.e. capital expenditure, overhead and maintenance fees, expertise required, consumables) and potential benefits (i.e. improvements to sensitivity, coverage, reproducibility, throughput, ease of use) to prioritize those with promise for chemical exposomics application. Alongside a need for technological investments (e.g. advanced hardware updates), numerous low-cost strategies showed high potential benefits (e.g. different column phases, enhanced sample fractionation) and are feasible for rapid adoption.